Optimization of Extraction Process of Polysaccharides from Microcos paniculata and Its Biological Activity Analysis - Qiuye LIU; Hui LIU; Xin CHEN; Yajie ZUO (Shipin gongye ke-ji, 2024)
Objective: To optimize the extraction process of polysaccharides from Microcos paniculata, and evaluate the antioxidant, antibacterial and pancreatic lipase inhibitory activities of Microcos polysaccharide. Methods: Ultrasonic-assisted extraction method was employed to extract polysaccharides from Microcos paniculata. The single-factor experiments were combined with orthogonal experiment to optimize the parameters of the extraction process. Antioxidant activity of Microcos polysaccharide was evaluated by DPPH, ABTS+, and OH free radical scavenging assays. The pancreatic lipase test was used to study the lipid lowering activity of Microcos polysaccharide. In addition, the antibacterial activity of Microcos polysaccharide against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Acinetobacter baumannii, and Klebsiella pneumoniae were measured by the micro broth dilution method. Results: The optimum conditions of Microcos polysaccharide were as follows: Ultrasonic power was 225 W, extraction temperature was 65 ℃, solid-liquid ratio was 1:20 (g/mL), extraction time was 35 min. Under these conditions, the yield of Microcos polysaccharide was 3.76%±0.25%. Microcos polysaccharide exhibited potent scavenging activity on DPPH, ABTS+ and OH free radicals, with the half-inhibitory concentrations were 0.1430, 0.01553 and 0.1451 mg/mL, respectively. The inhibition rate of pancreatic lipase was 36.22%±1.76%, when the concentration of Microcos polysaccharide was 5 mg/mL. The minimum inhibitory concentrations of Microcos polysaccharide against P. aeruginosa was 50 mg/mL, against E. coli and K. pneumoniae were all 100 mg/mL, against A. baumannii was 200 mg/mL. Conclusion: The extraction process optimized by single factor experiments combined with orthogonal experiment could effectively extract Microcos polysaccharides. The Microcos polysaccharide revealed good antioxidant and antibacterial as well as potential pancreatic lipase inhibitory activities, which would be valuable for in-depth developmental research.